A case report on placental chorioangioma - Barde, Kalyani P.; Aher, Gautam S.; Gavali, Urmila G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Chorioangioma is the term used to describe an abnormal proliferation of vessels arising from chorionic tissue, which is most commonly observed in the third, and less frequently in the second trimester of pregnancy as a solitary nodule or, less commonly, as multiple nodules. We here report a case of placental chorioangioma which presented as a case of preterm labour. 21 year old primigravida presented to us at 26 weeks of gestation with history of PV leak and pain in abdomen. Ultrasound showed a single live foetus corresponding to 24-26 weeks of gestation with amniotic fluid index (AFI): 5 cm (oligohydramnios) there was evidence of 58×42 mm heterogeneously hypoechoic lesion noted over placenta likely s/o chorioangioma. Patient went into spontaneous preterm labour on day 5 and delivered vaginally. Placenta weighted 700 gm. A globular mass of size 6×7 cm was attached to foetal surface of placenta with a pedicle with confirmed the finding of ultrasonography. Placental chorioangioma is associated with high rates of perinatal complications. Most complications may appear early and delivery is problematic due to prematurity. Thus better prenatal investigations and regular follow up is required for early diagnosis and treatment.